2013
DOI: 10.1159/000349909
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Alcohol-Related Video Sequences on Functional MRI in Abstinent Alcoholics

Abstract: The object of this study was the identification of brain areas that were significantly more connected than other regions with a previously identified reference region, the posterior cingulate cortex, during the presentation of visual cues in alcoholics. Alcohol-related and neutral video sequences were presented to 30 alcoholics who had been abstinent for at least 4 days. Participants underwent a psychometric assessment before and after the presentation of the video sequences. Functional MRI data were acquired.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…A recent meta-analysis of fMRI studies using alcohol cue reactivity demonstrated BOLD activation in several brain regions in AUD patients [19,20], including the PCC and precuneus. This observation suggests that PCC plays an important role in addiction and relapse [21]. When the PCC is activated by a visual stimulus, information from episodic memory is extracted and integrated with existing knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis of fMRI studies using alcohol cue reactivity demonstrated BOLD activation in several brain regions in AUD patients [19,20], including the PCC and precuneus. This observation suggests that PCC plays an important role in addiction and relapse [21]. When the PCC is activated by a visual stimulus, information from episodic memory is extracted and integrated with existing knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…However, no area showed significant subcortical volume regain within the first 14 days of abstinence in ADPs. (2) In ADPs, the cortical volume recovery during the first 2 weeks of abstinence is predominantly driven by an increase in CTh. No significant longitudinal change in SA was seen either on a global or local level.…”
Section: Discussionmentioning
confidence: 98%
“…In summary, the main aims of our present study are (1) to test (with Freesurfer) which parts of the subcortical regions are affected by excessive alcohol consumption and undergo significant recovery within the first 2 weeks of abstinence in alcohol-dependent patients (ADPs); (2) to gain a deeper insight into the underlying mechanisms that contribute to dynamic cortical volumetric changes in ADPs within the first 2 weeks of abstinence [8] by examining the CTh and SA; (3) to test whether and how the pattern of gyri and sulci are differentially affected by excessive alcohol consumption, and whether the extents of recovery are different. ication in the past 3 months, positive urine drug tests, brain injury history, other neurological or severe physiological illness (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta-analysis of fMRI studies using alcohol cue reactivity demonstrated BOLD activation in several brain regions in AUD patients [19,20], including the PCC and precuneus. This suggested that the PCC plays an important role in addiction and relapse [21]. When the PCC is activated by a visual stimulus, we extract information from our episodic memory and integrate this with existing knowledge.…”
Section: Discussionmentioning
confidence: 99%